Joining the ideational and the material: transforming food systems toward radical food democracy - Leitheiser, Stephen; Vezzoni, Rubén (Frontiers in Sustainable Food Systems, 2024)
This paper presents a conceptualization of radical food democracy (RFD) which links the diverse economies approach of Gibson-Graham with Tully’s notion of diverse citizenship. Despite its invaluable contribution to theorizing the role of alternative food networks (AFNs) in transforming unsustainable industrial food systems, the diverse economies scholarship has been criticized for essentializing the autonomy of alternative economic practices—hence risking to confound emancipatory social change with punctuated forms of “local,” “quality,” “organic certified” products, which nevertheless remain embedded in market-mediated capitalist relations, and displacement and/or deferral of negative impacts. This paper aims to address such critiques, contending that the realization of RFD requires both (1) the experimentation with new economic practices that carve out food economies alternative to the working logic of capital accumulation, and (2) the cultivation of new political subjects capable of universalizing these particular struggles. After situating various existing practices associated with food democracy in a framework of various modes of democratic citizenship, we underpin our understanding of RFD with a theory of change informed by Bob Jessop’s strategic-relational approach to social structures, agents’ reflexive actions, and their contingency. Following a critical scientific approach to the social role of academics, this theoretical framework is illustrated using a case study from Germany. The empirical work draws on participant observation and semi-structured interviews with leaders of Community Supported Agriculture (CSA) cooperatives and Food Policy Council (FPC) networks conducted in Cologne, Berlin, and Frankfurt in 2018–2020. To conclude, this paper argues that the emancipatory potential of food democracy should cultivate both lighthouse alternative economic practices that are connected with people’s everyday lives, and political imagination that dares to critically engage with existing institutions. Likewise, RFD praxis requires a constant back and forth between the ideational and the practical, the abstract and the concrete, the actionable and the analytical, to challenge both the symbolic-discursive and the material dimensions of capitalist agri-food systems.